Hot Tensile Deformation Behavior of Mg-4Li-1Al-0.5Y Alloy - Yang, Ting; Li, Zhuohua; Wang, Jinhui; Jin, Peipeng (Frontiers in Materials, 2021)
The microstructure evolution and deformation mechanism of the as-extruded-annealed Mg-4Li-1Al-0.5Y alloy (denoted as LAY410) were investigated during the hot tensile deformation at the temperatures between 150°C and 300°C with strains from 8 × 10−5 s−1 to 1.6 × 10−3 s−1. The results show that when the strain rate decreases and/or the deformation temperature increases, the peak stress of the alloy gradually decreases, and the elongations to fracture gradually increases. The true stress–strain curves show typical dynamic recrystallization (DRX) softening characteristics. It is observed that the microstructure in the magnesium (Mg) alloy deformed at 150°C is mainly composed of the deformed grains and a few recrystallized grains. The microstructures in the Mg alloy deformed at 200°C consisted of substructures and a slightly increasing number of dynamic recrystallized grains. When the deformation temperature reaches 250°C, the number of recrystallized grains increases significantly, and the microstructures are dominated by recrystallized grains. Moreover, through theoretical calculation and result analysis, the activation energy was about 99.3 kJ/mol, and the hot tensile deformation mechanism was the alternate coordinated deformation mechanism among grain boundary slip (GBS), intragranular slip, and DRX.